Placemaking through guerilla gardens at the TOKI mass housing grounds in Bor (Niğde) - Ufuk Soyöz (City, Territory and Architecture)
Abstract This paper investigates the guerilla gardens at the TOKI compound in Bor, Niğde, that add a vernacular touch to modern mass housing. TOKI, short for Turkish Republic Mass Housing Administration, was established to eradicate gecekondu, informal settlements that emerged in metropolitan cities in the 1950s due to rural-to-urban migration. Tasked with providing affordable housing for low-income families, TOKI implements standardized designs across Turkey's cities and towns, including the Bor (Niğde) complex. As opposed to the rigidity and uniformity of TOKI blocks, the architecture of guerilla gardens displays the spontaneity and ingenuity that characterized the original gecekondu. The research seeks answers to the questions of why guerilla gardens emerge at the Toki grounds, especially because TOKI was initially designed to eradicate vernacular gecekondu and what needs of the inhabitants these gardens accommodate. To answer these questions, ethnographic inquiry is conducted with the users of the guerilla gardens. Through the lens of the Bor TOKI residents' initiative, this paper offers insights into how vernacular input can inform future mass housing projects, possibly leading to more inclusive models that prioritize environmental sustainability while also respecting local lifestyles.